Phylogenomic and Evolutionary Analyses Reveal Diversifications of SET-Domain Proteins in Fungi - Guoqing Ding; Liqiu Shang; Wenliang Zhou; Siyi Lu; Zong Zhou; Xinyi Huang; Juan Li (Journal of Fungi, 2022)
In recent years, many publications have established histone lysine methylation as a central epigenetic modification in the regulation of chromatin and transcription. The histone lysine methyltransferases contain a conserved SET domain and are widely distributed in various organisms. However, a comprehensive study on the origin and diversification of the SET-domain-containing genes in fungi has not been conducted. In this study, a total of 3816 SET-domain-containing genes, which were identified and characterized using HmmSearch from 229 whole genomes sequenced fungal species, were used to ascertain their evolution and diversification in fungi. Using the CLANS program, all the SET-domain-containing genes were grouped into three main clusters, and each cluster contains several groups. Domain organization analysis showed that genes belonging to the same group have similar sequence structures. In contrast, different groups process domain organizations or locations differently, suggesting the SET-domain-containing genes belonging to different groups may have obtained distinctive regulatory mechanisms during their evolution. These genes that conduct the histone methylations (such as H3K4me, H3K9me, H3K27me, H4K20me, H3K36me) are mainly grouped into Cluster 1 while the other genes grouped into Clusters 2 and 3 are still functionally undetermined. Our results also showed that numerous gene duplication and loss events have happened during the evolution of those fungal SET-domain-containing proteins. Our results provide novel insights into the roles of SET-domain genes in fungal evolution and pave a fundamental path to further understanding the epigenetic basis of gene regulation in fungi.